Linearization circuit for transducers for nonlinear reponses - Khan, Sheroz; Jaafar, Aisyah; Abdullah Asuhaimi, Fauzun; Mohamad, Norshahida; ., Nurul Syuhada; Arfani, Izwan; Ismail, Siti Shukrina; Alam, A. H. M. Zahirul; Khalifa, Othman Omran (2010)
Thermistors are nonlinear transducers, and have found wide application in temperature measurement and control in different fields, but they exhibit a strong nonlinearity of the characteristic, which is of an exponential type. This project investigates the possibility of creating a thermistor-based temperature sensor with frequency and analog outputs and a linearized characteristic on the basis of a 555 timer.